Xây dựng hệ thống bài tập rèn luyện kĩ năng trình bày ý kiến về một vấn đề xã hội cho học sinh lớp 8 theo lí thuyết về giao tiếp của V. P. Dakharov - Đinh, Thuỳ Linh; Đỗ, Phương Thảo (Tạp chí Giáo dục, 2025)
The implementation of teaching and assessing speaking skills according to the 2018 General Education Program still faces many challenges. Particularly when encountering social-related topics, both teachers and students are lacking learning materials. On the other hand, V.P.Dakharov's communication theories can be applied to develop a system of exercises for training speaking skills for students. The article examines the factors that influence the communication process, as well as the competencies and skills in communication from the perspective of V.P. Dakharov. This study indicates that the application of V.P.Dakharov's communication theory is highly effective in building a system of exercises to train 8th-grade students' skills in presenting opinions on social issues. In practice, after implementing the system of exercises, students not only developed their general communication skills but also particularly honed important skills in presenting opinions on social issues.